Episodic Memories Among Irritable Bowel Syndrome (IBS) Patients: An Important Aspect of the IBS Symptom Experience - Sayuk, Gregory S.; North, Carol S.; Pollio, David E.; Gott, Britt M.; Alpers, David H. (Frontiers in Pain Research, 2022)
Objective: Some IBS patients possess detailed memories of the events surrounding their bowel symptom onset (“episodic memories”). In this exploratoey study we sought to: 1) examine memory relationship with gastrointestinal (GI) symptom severity, extraintestinal symptoms, and mood; 2) qualitatively explore memory valence and content in IBS patients with or without episodic memories. Methods: Referral IBS patients n=29; age 47.0± 2.2 years, 79.3% female) enrolled in this cross-sectional, mixed methods research study. Participants completed validated specific memory instruments [Autobiographical Memory Test (AMT), Sentence Completion for Events from the Past Test (SCEPT)] and relevant questionnaires [IBS symptoms 10-cm visual analog scale) ; SF-36 Health-related quality of life (HRQOL); Perley-Guze and PHQ-15/12: somatization; Beck Depression/Anxiety Inventories). Qualitative analysis examined the content and valence of general memories. Results: 14/29 (48.3%) of IBS subjects endorsed episodic memories of IBS symptom onset, often GI infections/enteritis (35.7%). Recall of the exact year (69%) and month (60%) of symptom onset were common. Episodic memories were associated with greater IBS symptom severity/bother, higher anxiety/depression, and poorer HRQOL. Though AMT and SCEPT memory specificity were not different based on episodic memories, overgeneralization to negatively-valenced cues in the AMT was associated with more severe IBS in those without episodic memory. Qualitative analysis revealed no observable differences in topic focus of IBS patients with and without episodic memories. Conclusions: IBS patients often endorse episodic memories associated with symptom onset, and this recall seems to associate with more severe symptoms. Overgeneralization responses to negative stimuli may lead to worse bowel symptoms in those without episodic memories. IBS memory specificity may associate with qualitative differences in processing psychosocial experiences and might be important to IBS pathophysiology.